Judicial Consideration of Disputes in the International Private Legal System (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article reviews and analyzes judicial consideration of disputes in the international private legal system. The features of alternative methods of resolving economic disputes in Uzbekistan relating to private international law will also be revealed. The experience of Uzbekistan in resolving economic disputes complicated by a foreign element will be studied.